Short-cut evaluation of pressure swing adsorption systems - Chung, Y; Na, BK; Song, HK (PERGAMON-ELSEVIER SCIENCE LTD, 1998)
A short-cut method is proposed to evaluate the performance of pressure swing adsorption (PSA) systems. The basic steps in PSA systems are categorized into the adsorption and desorption steps. Each step is mathematically modeled under the assumption of adsorption equilibrium in a batch mode. It easily generates the relation between compositions of the feed and the product of the whole PSA system which can be used just like the x-y diagram in liquid-vapor equilibrium processes; It is also useful in the design of bed couplings through-recycle and/or cascade of its product. It would be used as a screening tool in adsorbent selections and process comparisons at the early design stage for PSA systems. (C) 1998 Elsevier Science Ltd. All rights reserved.